Benign tumours of the maxilla: A comparative study of the clinical and radiographic anatomical limits of 32 cases collected at the odonto-stomatological consultation and treatment centre - Attogbain Patrice Kouamé; Daniel Amantchi; Wendpouiré Patrice Laurent Guiguimdé; Vazoumana Kouyaté (Elsevier, 2022)
Background: The benign tumour of the maxilla is characterised by a slowly evolving swelling and usually painless symptoms. It is the object of a consultation in Odontostomatology in Africa when it becomes voluminous causing a significant aesthetic damage.In practice, modern imaging (CT) and, failing that, panoramic imaging of the jaws remain the best means of assessing the size and extent of the tumour, with definitive diagnosis requiring clinical, radiological and histological observations. Objective: The aim of this study was to investigate the clinical and radiographic aspects of benign maxillary tumours diagnosed at the Centre de Consultations et de Treatments Odonto-Stomatologiques (CCTOS). Methods: Our study is descriptive and included 32 records based on clinical examination and panoramic radiography of the maxilla of patients admitted to the Department of Surgery and Odontological and Maxillofacial Pathologies of the CCTOS during one year. Résults: It was revealed that of the 32 cases of benign tumours, a female preponderance was observed with an average age of 30.72 years. The predisposition of the location was the right mandibular corpus of the patient. The radiographic images were large bone lyses, well limited but with inconsistent rhizoses. Conclusion: Our study showed the delay of clinical symptomatology on the radiographic image in the diagnosis of benign maxillary tumours and the frequency of bulky bone tumours.